2020
DOI: 10.1111/cod.13626
|View full text |Cite
|
Sign up to set email alerts
|

Surgical mask dermatitis caused by formaldehyde (releasers) during the COVID‐19 pandemic

Abstract: Institutional repository IRUAThis article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as doi: 10.1111/cod.13626 Surgical mask dermatitis caused by formaldehyde (releasers)during the COVID-19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 8 publications
(5 reference statements)
0
68
0
2
Order By: Relevance
“…2 A case of occupational allergic contact dermatitis caused by formaldehyde and 2-bromo-2-nitropropane-1,3-diol (bronopol) contained in a polypropylene surgical mask was published. 3 In another Chinese study, it was observed a significant increased flare of acne in individuals with long-time mask wearing (>4 hours per day over 2 months). The authors hypothesized that this condition is due to high temperature of the face covered by the mask that induces an increased sebum excretion rate: The latter increases by 10% for each 1°C rise.…”
Section: Dear Editormentioning
confidence: 95%
See 2 more Smart Citations
“…2 A case of occupational allergic contact dermatitis caused by formaldehyde and 2-bromo-2-nitropropane-1,3-diol (bronopol) contained in a polypropylene surgical mask was published. 3 In another Chinese study, it was observed a significant increased flare of acne in individuals with long-time mask wearing (>4 hours per day over 2 months). The authors hypothesized that this condition is due to high temperature of the face covered by the mask that induces an increased sebum excretion rate: The latter increases by 10% for each 1°C rise.…”
Section: Dear Editormentioning
confidence: 95%
“…In the last few weeks, some articles have been published on cases of dermatitis of the face associated with the use of anti‐COVID‐19 masks 1‐5 . In a Chinese study, it was observed that 49% of subjects reported skin reactions on the face related to mask.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 illustrates peri-auricular ACD related to surgical mask wear and positive PT reaction to textile dye mix at the 72-h reading. Other identified contact allergens include polyurethanes (toluene-2,4-diisocyanate, 4,4′-diaminodiphenylmethane, hexamethylene diisocyanate) and formaldehyde-releasing preservatives (formaldehyde, 2-bromo-2-nitropropane-1,3-diol) [ 97 , 98 ]. Trace amounts of formaldehyde can be present in polypropylene masks as a degradation by-product [ 99 ].…”
Section: Dermatologic Conditions Related To the Covid-19 Pandemicmentioning
confidence: 99%
“…Unlike irritant contact dermatitis, body parts other than the contact area are also involved as in this case such as forehead and neck. A case with facial ACD due to formaldehyde and bronopol in a polypropylene surgical mask mimicked a flare-up of rosacea (12).…”
Section: Discussionmentioning
confidence: 99%